Device for the Experimental Determination of Control Objects' Mathematical Models; Advanced Materials Research; Vol. 650 : Advances in Materials Science and Engineering - Goncharov V. I. Valery Ivanovich (2013, 2013)
Authors review methods of determining a plant's mathematical model. Then, they show a numerical method of pulse automatic control systems' (ACS) identification, focused on computer technology, the interpolation procedure and iterative methods of approximation to the desired solution. The basis of the approach is the method of inverse problems of dynamics and real interpolation method for calculating the linearized dynamical systems. An algorithm and the mobile device designed for the identification of facilities management in operational conditions are proposed. There is results' application in the conclusion.